Las áreas marinas protegidas como asunto de política internacional: el escenario de la Comisión para la Conservación de los Recursos Vivos Marinos Antárticos - Lorenzo, Cristian; Seitz de Graziano, Ana E.; Navarro Drazich, Diego (2019)
In 2016, the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR) created a Marine Protected Area (MPA) in the Ross Sea. The purpose of this article is to know the United Kingdom, the United States and New Zealand stance on this decision, regarding the impacts global warming on the Antarctic geopolitics and the discussions on the establishment of new MPAs in the CCAMLR’s scope. A qualitative methodology was used for this purpose through an inductive approach. Documents and materials published by the CCAMLR and by the three countries were analyzed. Everything was supplemented by performing semi-structured interviews with key actors. The paper concludes that the stance of the United Kingdom, the United States and New Zealand on the CCAMLR, when a MPA was designated in the Ross Sea, requires understanding the context of the political impact of global warming on Antarctic geopolitics and the debates to designate new MPAs. It is also necessary to consider the strategic interests of these countries in the CCAMLR’s area of application, their views on the MPA debate, the geopolitical component of their relevant strategies for marine conservation of biodiversity and, finally, the impacts of changes in international policy on existing environmental commitments. Em 2016, a Comissão para a Conservação dos Recursos Vivos Marinhos Antárticos (CCRVMA), criou uma área marinha protegida (AMP) no Mar de Ross. Este artigo tem como objetivo conhecer o posicionamento do Reino Unido, Estados Unidos e Nova Zelândia diante dessa decisão, no contexto dos efeitos do aquecimento global na geopolítica antártica, e as discussões em torno do estabelecimento de novas AMPs no campo da CCRVMA. Por isso, foi utilizada uma metodologia qualitativa sob uma perspectiva indutiva. Os documentos e materiais publicados pela CCRVMA e pelos três Estados foram analisados. Tudo isso foi complementado por entrevistas semiestruturadas realizadas com os principais atores. O artigo conclui que o comportamento do Reino Unido, Estados ...